Surface and New Building Deformation Analysis of Deep Well Strip Mining - Yuanzhong Luan; Yue Dong; Yanhe Ma; Liyuan Weng (Advances in Materials Science and Engineering)
Aiming at the problem of surface movement and long-term stability of a work plane of deep well strip mining in Shandong Province, an observation station is set up on the surface of strip mining, and the surface deformation value during strip mining is measured with advanced measuring instruments; on the stable surface of the old mining area, the surface deformation monitoring work is also carried out for new buildings. In addition, the FLAC3D simulation method is used to determine the subsidence factor of different mining depth, mining width, mining length, and mining thickness, and the mathematical model between the subsidence factor and mining depth, mining width, mining length, and mining thickness is established. After the surface of the old goaf is basically stable after strip mining, the high-rise buildings are built. By changing the size of the new buildings and the amount of the load imposed on the surface, the surface deformation is simulated and calculated, and the relationship between the different load positions, load sizes, loading building sizes, and the surface activated deformation is obtained. The measured value of the surface deformation confirms that the load of the new buildings can induce the activation of the old goaf and make the surface generate secondary deformation, but the activated deformation makes the new building within the range of 1, so the new building is safe.